Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.5210/fm.v15i12.3208
|View full text |Cite
|
Sign up to set email alerts
|

The size distribution of open access publishers: A problem for open access?

Abstract: I stumbled across the question of publisher size while preparing for an earlier article. From the viewpoint of an economist, the size distribution of Open Access publishers looked inefficient. In this article I first explore reasons to be sceptical to a situation with a large number of small publishers. Then I go through the numbers from the Directory of Open Access Journals, also discussing problems inherent in the material. The results are then compared to similar data about Toll Access publishing. A conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 0 publications
1
17
3
2
Order By: Relevance
“…The finding that most journals are published either by publishers with many journals using OA APCs (50 journals plus) or very few journals (1-9 with one-off journals being the largest single category by far) supports the distribution found by Frantsvåg in 2010 [16]. Frantsvåg considered the large number of small publishers as a problem.…”
Section: Discussionsupporting
confidence: 69%
“…The finding that most journals are published either by publishers with many journals using OA APCs (50 journals plus) or very few journals (1-9 with one-off journals being the largest single category by far) supports the distribution found by Frantsvåg in 2010 [16]. Frantsvåg considered the large number of small publishers as a problem.…”
Section: Discussionsupporting
confidence: 69%
“…He found that the distribution was strongly skewed, with nearly 90% of publishers represented by only one journal title and larger publishers representing only a quarter of the titles in the directory. Arguing from the point of view of economic theory, Frantsvåg 50 concluded that the high proportion of singlejournal OA publishers is a sign of an ineffi cient OA marketplace since they cannot take advantage of economies of scale in production and distribution. In his words: ' All these elements suggest that small-scale operation of OA publishing is economically ineffi cient, and that OA publishing best be organized in larger publishing institutions.'…”
Section: Discussionmentioning
confidence: 99%
“…Frantsvåg 50 analyzed the distribution of journals by publisher in DOAJ. He found that the distribution was strongly skewed, with nearly 90% of publishers represented by only one journal title and larger publishers representing only a quarter of the titles in the directory.…”
Section: Discussionmentioning
confidence: 99%
“…Une étude récente a démontré que le secteur OA est dominé par des éditeurs de petite taille qui souvent ne publient qu'un seul titre (Frantsvåg, 2010). Neuf éditeurs sur dix font partie de cette catégorie, et seulement 25% des revues OA sont publiées par des éditeurs plus importants.…”
Section: Introductionunclassified
“…L'article réunit un certain nombre d'éléments sur la distribution des éditeurs de revues en libre accès en fonction de leur taille afin d'évaluer l'impact de cette distribution sur l'édition scientifique. L'article a trois objectifs : consolider l'étude de Frantsvåg (2010) sur la distribution des éditeurs de revues OA avec des données de 2011 ; identifier l'évolution de la situation depuis 2010 ; et étudier plus particulièrement le marché des revues OA en France. Il contribue ainsi à l'analyse et à la compréhension économique de l'édition scientifique en général et du libre accès en particulier ; l'article décrit en parallèle d'autres approches comme l'analyse des coûts de production, des subventions, du retour sur investissement, de la structure de l'offre du marché etc.…”
Section: Introductionunclassified